2008
DOI: 10.1007/s10549-008-9890-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of magnetic resonance imaging, multidetector row computed tomography, ultrasonography, and mammography for tumor extension of breast cancer

Abstract: MR imaging was the most accurate breast imaging modality for the tumor exten of breast cancer, although MR imaging had a substantial of risk of overestimation. MR imaging, MDCT and US can complement MMG for the preoperative evaluation of patients who are candidates for breast-conserving surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 28 publications
2
69
2
Order By: Relevance
“…Similarly, Kapenhas-Valdes et al [16] also found that 5 patients (8.8%) who were found to have carcinoma (one of them had invasive cancer and the remaining ones had DCIS or LCIS) with ductoscopy-guided cytopathology had benign and stable findings via breast imaging (MG and US). The accuracy of US and MG is 61 and 22%, respectively, for noncomedo DCIS [70]. MG, US, and routine touch cytology of the nipple discharge are not sensitive in detecting DCIS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kapenhas-Valdes et al [16] also found that 5 patients (8.8%) who were found to have carcinoma (one of them had invasive cancer and the remaining ones had DCIS or LCIS) with ductoscopy-guided cytopathology had benign and stable findings via breast imaging (MG and US). The accuracy of US and MG is 61 and 22%, respectively, for noncomedo DCIS [70]. MG, US, and routine touch cytology of the nipple discharge are not sensitive in detecting DCIS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, also in the analysis of histological factors, a large DCIS lesion was described to be associated with invasion [1,2]. In the DCIS, MR imaging was reportedly more sensitive for detection of the lesion, with higher accuracy for determining the extent of disease than mammography [15, 27,28]. Thus, to estimate histological lesion size, overall, MR imaging was more reliable than mammography.…”
Section: Discussionmentioning
confidence: 99%
“…MRI achieves the highest sensitivity of all imaging modalities in breast cancer detection reaching 99% [9][10][11][12][13][14][15][16]. MRI has been proven to represent an accurate method in the pre-therapeutic cancer staging for determining the exact tumor size as well as depicting multifocality and multicentricity [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%